Amino Acid sequence analysis of the two major outer Capsid Proteins (VP7 and VP4) from human-derived canine G3P[3] Rotavirus Strain Detected in Brazil - Luchs, Adriana; Timenetsky, Maria do Carmo Sampaio Tavares (Journal of Health & Biological Sciences, 2013)
Introduction: A close look at the rotavirus group A (RVA) genotypes in Brazil revealed the detection of a rare G3P[3] strain close related to canine strains. The aim of this study was to add to the already known genetic analysis by the description of the G3P[3] (IAL-R2638 strain) amino acid characteristics. Methods: Amino acid sequence analysis and protein based trees were conducted using BioEdit and MEGA 4.0. Results: The VP7 and VP4 protein of the IAL-R2638 strain displayed the highest amino acid identity to the canine-derived human strain HCR3A (99.2%), and to the canine strain RV52/96 (96.4%), respectively. IAL-R2638 strain did not possess an extra VP7 N-linked glycosylation site at amino acid 238 recently described for some G3 strains, as well as RotaTeqTM G3 vaccine strain. The topology exhibited by phylogenetic trees in previous analysis were maintained in the present amino acid-based trees, reinforcing a stable relationship between G3P[3] strains. Conclusions: Amino acid analysis data were consistent with the previous sequence of data obtained for the IAL-R2638 strain, supporting its possible canine origin. Theoretically, RotaTeqTM vaccine could efficiently protect against G3P[3] infections based on the lack of the extra VP7 N-linked glycosylation site at amino acid 238. Phylogenetic analysis hypothesizes that all features undergo evolution independently of each other; however, unfavorable effects of nucleotide substitutions may be compensated by substitutions in other positions. The present study raises the question as to whether the amino acid-based trees could be applied as an approach to the study of RVA evolution, avoiding incorrect phylogenetic reconstructions.